Optimalisasi Pembelajaran Melalui Pemahaman Kemampuan Awal Peserta Didik - Khofifah Dwi Wulandari; Anifa Wardah; Lailatus Syarifah; M. Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Identifying learners' initial abilities is a key step in learning. This article describes six important indicators that can help an educator to identify learners' initial abilities. Like a chef planning a family meal, a teacher needs to understand the unique needs and abilities of each learner. Every learner has an initial ability, an ability that has been possessed before acquiring specific new end abilities Initial skills represent the learner's current level of knowledge and skills to achieve the future status that the educator expects from the learner. To analyze students' initial abilities, at least an educator can identify the initial abilities of students by using techniques to detect initial abilities. In addition, educators can know well the learning styles of different students. The ability of educators to analyze students' initial abilities affects the learning methods they develop, which ultimately results in superior learning outcomes.